2007
DOI: 10.3201/eid1303.060403
|View full text |Cite
|
Sign up to set email alerts
|

EnvironmentalBurkholderia cepaciaComplex Isolates from Human Infections

Abstract: Members of the Burkholderia cepacia complex (Bcc), found in many environments, are associated with clinical infections. Examining diverse species and strains from different environments with multilocus sequence typing, we identified >20% of 381 clinical isolates as indistinguishable from those in the environment. This finding links the natural environment with the emergence of many Bcc infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 14 publications
1
98
0
4
Order By: Relevance
“…161,[298][299][300] Strains identical to those found in people with CF have also been isolated from onions and onion rot. 301,302 Furthermore, MLST analysis demonstrated that more than 20% of 381 CF isolates of Burkholderia were indistinguishable from strains recovered from the natural environment. 301 B. cepacia complex isolates with the same nucleotide identity at all 7 MLST loci have been isolated from people with CF and from river water, suggesting another possible environmental reservoir.…”
Section: Iiid1 Nonhealthcare Sources: Soil Organic Matter and Watermentioning
confidence: 99%
See 1 more Smart Citation
“…161,[298][299][300] Strains identical to those found in people with CF have also been isolated from onions and onion rot. 301,302 Furthermore, MLST analysis demonstrated that more than 20% of 381 CF isolates of Burkholderia were indistinguishable from strains recovered from the natural environment. 301 B. cepacia complex isolates with the same nucleotide identity at all 7 MLST loci have been isolated from people with CF and from river water, suggesting another possible environmental reservoir.…”
Section: Iiid1 Nonhealthcare Sources: Soil Organic Matter and Watermentioning
confidence: 99%
“…301,302 Furthermore, MLST analysis demonstrated that more than 20% of 381 CF isolates of Burkholderia were indistinguishable from strains recovered from the natural environment. 301 B. cepacia complex isolates with the same nucleotide identity at all 7 MLST loci have been isolated from people with CF and from river water, suggesting another possible environmental reservoir. 302 Finally, B. cenocepacia and Burkholderia vietnamiensis have been isolated from human sewage in the United Kingdom, but genotyping of these isolates was not performed.…”
Section: Iiid1 Nonhealthcare Sources: Soil Organic Matter and Watermentioning
confidence: 99%
“…All BCC species can be isolated from clinical samples as well as from the natural environment, which could be acting as a constant "reservoir" for infectious BCC pathogens [16]. Furthermore, most BCC species include isolates of both clinical and environmental origin showing the same sequence type (ST) by multi locus sequence typing (MLST), i.e.…”
Section: Pathogenicity Of Burkholderia Speciesmentioning
confidence: 99%
“…Evidence for this assumption was presented in a recent transcriptomic study of the oral bacterium Porphyromonas gingivalis, which, when exposed to H 2 O 2 , demonstrated concerted overexpression of one IS family (4). The aims of our study were (i) to characterize the distribution of selected IS elements in the Czech epidemic strain CZ1 (designated ST-32 by MLST [1]), (ii) to evaluate their possible link to the heterogeneous fingerprints of CZ1 generated by PFGE, and (iii) to examine whether oxidative stress conditions promoted the movement of IS elements within the genomes of strain CZ1 and the sequenced B. cenocepacia strain J2315 (ST-28).…”
mentioning
confidence: 99%